CEO financial background, managerial ownership, and corporate innovation: Insights from imprinting theory - Gao, Yu; Tang, Yahao; Zhang, Jiruo (Frontiers in Psychology, 2023)
The global ecological environment is facing increasingly severe challenges; therefore, it is crucial to implement sustainable development policies and promote corporate innovation. Based on imprinting theory, we examine the relationship between CEO financial background and corporate innovation within the Chinese context. The results confirm that CEOs with a financial background negatively impact corporate innovation, while managerial ownership mitigates this effect. Existing literature has considered the impact of CEO background on corporate innovation; however, it mainly takes up corporate innovation from the perspective of upper-echelon theory. In addition, the mechanism of CEO financial background on corporate innovation is ambiguous in the Chinese cultural context. This study enriches the literature on the relationship between the characteristics of CEO background and corporate behavior, thereby offering guidance for corporate innovation practices.